Dialectic and refutation in Plato's Sophist Dialéctica y refutación en el Sofista de Platón - Spangenberg, Maria del Pilar (2020)
The dialectic exhibited in Plato's dialogues assumes different characters throughout the corpus. Nevertheless, it remains always linked to refutation. In this way, like dialectic, refutation assumes different characteristics. The aim of this work is to show how refutation takes a key role in the Sophist, even with unique features: far from facing an opponent of flesh and blood as in Socratic dialogues, the Eleatic Stranger faces hypotheses, and instead of examining consistence within the opponent's beliefs, he draws upon a radical mechanism that focuses in the conditions of possibility of the (opponent's) discourse.